A DIFFERENTIAL CATALOGUE OF RIGHT ASCENSIONS OF 263 RRS2 STARS OBTAINED FROM OBSERVATIONS MADE WITH THE ODESSA MERIDIAN CIRCLE IN 1990-1993 - Chelombit’ko, A. P. (Одеські астрономічні публікації, 2017)
This catalogue contains the results of 1321 right ascensions observations of 2dj Radio References Stars obtained al Odessa with the Repsold transit circle in 1990-1993. The precise positions of these stars are necessary lo establish a connection between the radio and optical systems of celestial coordinates (CONFOR program). All observations were made by author in the differential way and reduced by formula Bessel in FK5 system. Each star was observed on the average five times. The positions are for equinox J2000.0 and for epoch of observations. The mean square error of catalogue position is 0s.007. This catalogue was sent to Astronomical Observatory of Kiev University for the inclusion in a summary catalogue.